Antioxidant, α-glucosidase, and nitric oxide inhibitory activities of six Algerian traditional medicinal plant extracts and 1H-NMR-based metabolomics study of the active extract - Hellal, Khaoula; Maulidiani, Maulidiani; Ismail, Intan Safinar; Tan, Chin Ping; Abas, Faridah (MDPI, 2020)
Claims of effective therapy against diabetes using plants including Peganum harmala L., Zygophyllum album, Anacyclus valentinus L., Ammodaucus leucotrichus, Lupinus albus, and Marrubium vulgare in Algerian empirical medicine prompted our interest in evaluating their antidiabetic activity by screening their free radical scavenging (DPPH), α-glucosidase, and nitric oxide (NO) inhibitory activities as well as the total phenolic content (TPC). Extracts of the selected plants were prepared using different ratios of ethanol (0, 50, 80, and 100%). In this study, 100%, and 80% ethanol extracts of L. albus were found to be the most potent, in inhibiting α-glucosidase activity with IC50 values of 6.45 and 8.66 μg/mL, respectively. The 100% ethanol extract of A. leucotrichus exhibited the highest free radical scavenging activity with an IC50 value of 26.26 μg/mL. Moreover, the highest TPC of 612.84 μg GAE/mg extract was observed in M. vulgare, extracted with 80% ethanol. Metabolite profiling of the active extract was conducted using 1H-NMR metabolomics. Partial least square analysis (PLS) was used to assess the relationship between the α-glucosidase inhibitory activity of L. albus and the metabolites identified in the extract. Based on the PLS model, isoflavonoids (lupinoisoflavone G, lupisoflavone, lupinoisolone C), amino acids (asparagine and thiamine), and several fatty acids (stearic acid and oleic acid) were identified as metabolites that contributed to the inhibition of α-glucosidase activity. The results of this study have clearly strengthened the traditional claim of the antihyperglycemic effects of L. albus.